FEATURES OF THE EDUCATIONAL PROCESS IN THE CONTEXT OF THE CORONAVIRUS PANDEMIC (BY THE EXAMPLE OF TEACHING CIVIL LAW) - M. A. Bychko; I. A. Komarevceva (Гуманитарные и юридические исследования)
The year 2020 became a special year both for our country and for the world community as a whole. The world is facing the threat of extinction due to the large-scale spread of the coronavirus infection COVID-19. The pandemic of a new coronavirus infection that has engulfed most countries of the world has become a modern challenge and has required states to take decisive steps in various areas, including optimizing the educational process in the face of the need to comply with restrictive measures. At the federal level, regulations were quickly adopted that served as the basis for the implementation of the educational process in the so-called remote mode, including the Order of the Ministry of Education of 17.03.2020 No. 103, which regulated the procedure for supporting the implementation of educational programs using e-learning and distance learning technologies. Russian education was forced to switch to online mode, after which the contact work of the teacher and the student became possible only in the electronic educational environment. The experience of teaching legal disciplines remotely, which has been formed by Russian teachers for several months, has brought to the surface a number of important issues and problems that require reflection and solution. Here are just a few of them: the lack of an optimal material and technical base for the participants of the educational process, both the student and the teacher; the lack of adequate methodological support for disciplines that would be designed for distance or at least for hybrid training. Many questions arise around the practical component of training, including how to most effectively organize practical classes for students when using e-learning and distance learning technologies; how ready the teacher is to teach remotely. The article presents the experience of teaching civil law in online education.